Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1530/eje-19-0801
|View full text |Cite
|
Sign up to set email alerts
|

A homozygous mutation in the highly conserved Tyr60 of the mature IGF1 peptide broadens the spectrum of IGF1 deficiency

Abstract: European Journal of Endocrinology 181:6 C32 Commentary M J E Walenkamp and J M Wit IGF1 deficiency https://eje.bioscientifica.comtesting in similar cases. The rapidly expanding use of hypothesis-free genetic testing in children with short stature will probably lead to the detection of more cases and a wider range of phenotypic variation. Declaration of interestThe authors declare that there is no conflict of interest that could be perceived as prejudicing the impartiality of this commentary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Patients with genetic IGF-1R defects, show symptoms (i.e., pre and postnatal growth retardation, microcephaly, cardiac defects and dysmorphic features) that significantly overlap with those presented in various CDG types [ 19 , 20 ]. For example, the majority of CDG patients analyzed in the present study showed growth failure and microcephaly (Supplementary Table 1), which are also clinical hallmarks of IGF-1/IGF-1R defects [ 36 38 ]. Further studies are needed, also taking advantage of the recently developed CDG animal models [ 28 ], to evaluate the impact of glycosylation defects on each component of the IGF-1 system.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with genetic IGF-1R defects, show symptoms (i.e., pre and postnatal growth retardation, microcephaly, cardiac defects and dysmorphic features) that significantly overlap with those presented in various CDG types [ 19 , 20 ]. For example, the majority of CDG patients analyzed in the present study showed growth failure and microcephaly (Supplementary Table 1), which are also clinical hallmarks of IGF-1/IGF-1R defects [ 36 38 ]. Further studies are needed, also taking advantage of the recently developed CDG animal models [ 28 ], to evaluate the impact of glycosylation defects on each component of the IGF-1 system.…”
Section: Discussionmentioning
confidence: 99%
“…GH de ciency/insensitivity and IGF1 de ciency play an important role in intrauterine linear and cranial growth [50]. The primary clinical features of a homozygous de cient IGF1 include perinatal growth restriction, severe microcephaly as well as severe global developmental delay [51].…”
Section: Discussionmentioning
confidence: 99%